RANCANG BANGUN RANGKA MOBIL TIPE URBAN CONCEPT BERPENUMPANG TUNGGAL DENGAN KAPASITAS MAKSIMUM 70 KG - Andre Krisna Putra; Susilo Adi Widyanto (JURNAL TEKNIK MESIN, 2015)
Ground transportation become transportation with most users. In Indonesia, particularly many emerging cheap cars, such as high school or equivalent education institutions that make their own cars, and the existence of the Shell Eco Marathon competition which includes urban concept category in competition. This background makes the author raised the topic of urban concept car type to be made in particularly frame parts. There is many types of frame such as ladder frame which is a widely used for SUV. This study aims to create a framework of urban concept car types and determine the level of security. The material used is steel ST37 which has a maximum tensile strength of 39 826000 N / m2 and a yield strength of  220594000 N / m2. The cutting process using a grinder, whereas the process of joining using electric welding. Frame consists of 6 pieces transverse frame and 2 pieces side frame. Load calculation using concentrated load by dividing the frame into 3 parts: the back, middle and front. In the calculation of the value obtained allowable stress and maximum stress design, which allowable stress must be greater than the stress that occurs in the design.The side frame using square metal frame with dimension 50x50x3,2 mm and transverse using L profile iron with dimension 40x40x5 mm angle iron.